Impact of social isolation caused by the COVID-19 pandemic on the mental health of the general population: An integrative review (Research, Society and Development, 2021)
Objective: to investigate the impact of the pandemic caused by COVID-19 on the mental health of the general population. Method: this is an integrative literature review, carried out by searching the PubMed, Web of Science, PsycINFO, Scopus, BVS and Scielo databases, using the descriptors "SARS-CoV-2"; "COVID-19"; "Coronavirus"; "Mental health"; "Population". 1538 articles were identified, of which 16 were included in this study. Results: The evidence found in the literature shows that individuals in social isolation are more susceptible to the stress caused by this condition and as a consequence of this social deprivation has mainly presented anxiety disorders, depressive disorders and changes in sleep quality. Feelings of anger, confusion and symptoms of post-traumatic stress were also observed, which may be associated with the period of prolonged social withdrawal, fear of contamination, frustration, lack of basic supplies, insufficient information and financial problems. Conclusion: coping with COVID-19 generated a change in society's way of life, making it necessary to prepare health services for this demand, so that there is psychological and social support and support from the general population, directing attention to the factors that trigger suffering psychic, supporting individuals in this period and in the post-pandemic.